Enhanced Production of Pediocin PA-1 and Coproduction of Nisin and Pediocin PA-1 by Lactococcus lactis - Horn, Nikki (American Society for Microbiology, 1999)
The production and secretion of class II bacteriocins share a number of features that allow the interchange of genetic determinants between certain members of this group of antimicrobial peptides. Lactococcus lactis IL1403 encodes translocatory functions able to recognize and mediate secretion of lactococcin A. The ability of this strain to also produce the pediococcal bacteriocin pediocin PA-1, has been demonstrated previously by the introduction of a chimeric gene, composed of sequences encoding the leader of lactococcin A and the mature part of pediocin PA-1 (N. Horn, M. I. Martínez, J. M. Martínez, P. E. Hernández, M. J. Gasson, J. M. Rodríguez, and H. M. Dodd, Appl. Environ. Microbiol. 64:818–823, 1998). This heterologous expression system has been developed further with the introduction of the lactococcin A-dedicated translocatory function genes, lcnC and lcnD, and their effect on bacteriocin yields in various lactococcal hosts was assessed. The copy number of lcnC and lcnD influenced production levels, as did the particular strain employed as host. Highest yields were achieved with L. lactis IL1403, which generated pediocin PA-1 at a level similar to that for the parental strain, Pediococcus acidilactici 347, representing a significant improvement over previous systems. The genetic determinants required for production of pediocin PA-1 were introduced into the nisin-producing strain L. lactis FI5876, where both pediocin PA-1 and nisin A were simultaneously produced. The implications of coproduction of these two industrially relevant antimicrobial agents by a food-grade organism are discussed.